Septemoecia a new genus of halocyprid ostracod (Myodocopa, Halocyprididae, Bathyconchoeciinae) for the seven-spined species formerly attributed to Bathyconchoecia - Angel, Martin V.; Brandåo, Simone N. (Zootaxa, 2018)
The five species with seven large carapace spines that were previously assigned to the genus Bathyconchoecia are re-classified in a new genus Septemoecia. Septemoecia longispinata (Ellis, 1987) (new combination) is designated as the type species. The previously unknown adult female of S. georgei (Kornicker & Rudjakov, 2004) (new combination) and adults of S. septemspinosa (Angel, 1970) (new combination) are described. Meristic and zoogeographical data are presented and a key to the species based on external carapace characters is provided.